2016
DOI: 10.18632/aging.101099
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary aerobic exercise increases arterial resilience and mitochondrial health with aging in mice

Abstract: Mitochondrial dysregulation and associated excessive reactive oxygen species (mtROS) production is a key source of oxidative stress in aging arteries that reduces baseline function and may influence resilience (ability to withstand stress). We hypothesized that voluntary aerobic exercise would increase arterial resilience in old mice. An acute mitochondrial stressor (rotenone) caused greater (further) impairment in peak carotid EDD in old (~27 mo., OC, n=12;−32.5±-10.5%) versus young (~7 mo., YC n=11;−5.4±- 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 100 publications
2
48
0
Order By: Relevance
“…Some studies that relate autophagy and/or mitochondrial function to the aging process show results that may be different [ 10 , 42 44 ]. Specifically, regarding proteins involved in biogenesis, most studies found a decrease in mRNA and protein expression of PGC-1 α [ 45 53 ]. These data indicate that, during aging, the reduced mitochondrial biogenesis may be due to the lack of response of PGC-1 α to different stimuli.…”
Section: Effects Of Aging On Mitochondrial Function and Mitophagymentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies that relate autophagy and/or mitochondrial function to the aging process show results that may be different [ 10 , 42 44 ]. Specifically, regarding proteins involved in biogenesis, most studies found a decrease in mRNA and protein expression of PGC-1 α [ 45 53 ]. These data indicate that, during aging, the reduced mitochondrial biogenesis may be due to the lack of response of PGC-1 α to different stimuli.…”
Section: Effects Of Aging On Mitochondrial Function and Mitophagymentioning
confidence: 99%
“…In this line, Mfn1 and Mfn2 also increased in mouse and rat muscles during senescence [ 43 , 44 , 48 , 59 61 ]. However, other studies point to an absence of changes or even decreases in these proteins responsible for mitochondrial fusion [ 30 , 45 , 46 , 58 , 60 , 64 66 ]. On the other hand, and as previously mentioned, mitophagy is promoted by fission [ 18 ].…”
Section: Effects Of Aging On Mitochondrial Function and Mitophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of exercise training through other mechanisms has been less considered, including changes in anti-aging hormones and oxidative stress, MAPKs may be involved in the hypertrophy of the middle-aged heart. In this context, it has also been reported that exercise training can be effective in improving age-related mitochondrial disorders (82,83).…”
Section: Effect Of Exercise Training On Middle-aged Hypertrophymentioning
confidence: 96%
“…Recently, mitochondrial reactive oxygen species (mtROS) have been implicated as a possible cause of the age-associated changes in arterial function and structure (Gioscia-Ryan, Battson, Cuevas, Zigler, & Sindler, 2016) (Dai, Rabinovitch, & Ungvari, 2012). As organisms age, the mitochondrial production of ROS increases in the vasculature because of a decline in overall mitochondrial function, declining activity of ROS scavenging enzymes, and mutations to mitochondrial DNA (Bratic & Larsson, 2013).…”
Section: Ros Mitochondria and Agingmentioning
confidence: 99%